Representing Education in Film How Hollywood Portrays Educational Thought, Settings, and Issues - Resnick, David (Palgrave Macmillan US, 2018)
This book presents an incisive analysis of how fundamental issues in education are portrayed in film. Focusing on recent films, the author draws on a wide range of educational thinkers and fields of research to examine issues not discussed before. Resnick challenges our assumptions and enriches our general knowledge on critical issues like funding for arts education, what we mean by successful civic education, and the educational value of sports. This project, which includes topics such as the gender gap in civic education, religious education, and what animated films have to say about human education, can serve as a "viewer's guide" to selected educational issues in film and may spur the intelligent use of films in public debate. .